Crash risk and ESG disclosure - Paulo Pereira da Silva (Borsa İstanbul Review, 2022)
This study examines whether ESG (environmental, social and governance) disclosure influences firm-specific crash risk. Our main research hypothesis postulates that further information disclosure about ESG activities and risks mitigates crash risk by virtue of lower opacity and information asymmetry between managers and outside investors (e.g., by facilitating the assessment of environmental and social risks and concerns faced by the firm). The analysis covers a global sample of firms and the period spanning 2007-2019. Overall, our findings confirm that ESG disclosure attenuates (future) firm-specific crash risk. The results are robust to different model specifications employed by previous research. The impact of ESG disclosure on crash risk is concentrated on firms from developed countries; benefits from ESG disclosure appear to be more limited in firms located in emerging markets and developing economies (EMDEs). Finally, the results from the decomposition of the ESG disclosure indicator suggest that all three dimensions (environmental, social and governance disclosure) weigh crash risk downwards.
Keywords: G10; G14; G30; M14; M40; 330; Crash risk; ESG; Non-financial disclosure